Bringing it all back home - DE MEYER, Arnoud Cyriel Leo (Institutional Knowledge at Singapore Management University, 2008)
There seems little thatcan be positive for the UK manufacturing sector in oil prices above $120 abarrel, rising costs of other natural resources, inflation and growingenvironmental pressure. But there may be a silver lining. Increased transportcosts resulting from higher energy prices and carbon taxes may create anopportunity for a revival in western manufacturing.